Faktor yang Mempengaruhi Penyembuhan Luka Perineum Pada Ibu Post Partum - Esti Handayani; Mundarti Mundarti; Siti Rofiah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
This research is analytic survey with cross-sectional research design. The populations in this study were all normal postpartum mother from 2 to 7 days after birth, non probability sampling using accidental sampling technique with 31 mothers are involved. Data collection technique is using questionnaire and checklist of healing perineum laceration process. Statistical analyses of the data using uni variate, bi variate test. Logistic regretion test are used for multivariate analyze. The results showed that there are no factors that are influenced to healing perineum laceration process of postpartum mother by value for Maternal age (p value = 0.699), educational background ( p value = 0,797 ), Parity (p value =0,875 ), Nutrition status (p value = 0,474) and Hemoglobin level by p value = 0,303. Eventhough that are no relationships among age, educational background, parity, nutrition status and hemoglobin but mother should concern about age and parity status duringpregnancy to avoid the complication during delivery baby.